The effect of magnetic field annealing on magnetic properties in ultrathin fe-based nanocrystalline alloys - Park, JY; Suh, SJ; Kim, KY; Noh, TH (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 1997)
Ultrathin Fe78Al4B12Nb5Cu1 and Fe83B9Nb7Cu1 nanocrystalline ribbon alloys below 10 mu m in thickness were annealed in transverse magnetic field, and then the high-frequency soft magnetic properties and their compositional effect were investigated. Very high effective permeability and excellent magnetic core loss characteristics in MHz range were obtained for both alloys after optimum annealing. However, the Al-added alloy was more sensitive to the magnetic field annealing and much improved soft magnetic properties in the high frequency range were revealed.